Effect of Soybean Seeds Freezing under the Effect of Cryoprotectants on a Sprouting Energy and Germinating Capacity - Shevchenko, N. O.; Strybul, T. F.; Zhmurko, V. V.; Kobyzeva, L. M. (Problems of Cryobiology and Cryomedicine, 2003)
We have investigated the effect of soybean seeds freezing down to -55 and -70°C under propanediol (PD), PEO-400 and PEO-1500 cryoprotectants’ effect. There were used various conditions of seeds treatment with cryoprotectants (variation with the concentrations, exposure term), various freezing regimens. It has been established that when selecting the optimum conditions for soybean seeds treatment with cryoprotectants it is possible not only to keep the primary biological characteristics of seeds, but also increase the indices for a sprouting energy and germinating capacity. We have also discussed the reasons for various effect of cryoprotectants on seeds planting characteristics.